2023
DOI: 10.1590/1980-5373-mr-2022-0302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fibers Orientation of the Different Types of Composite Plates Notched of U-Shape Repaired by Composite Patch

Abstract: The main objective of this work is to repair a structure of composite materials by gluing composite patches with different fiber directions. The effects of stress distribution, damaged area ratio, stress intensity factor KIC and imposed stacking sequence were highlighted by a comprehensive study that contained two sides, an applied experimental side and a numerical model side. The composite materials plates studied in this work are 8-layer of graphite/epoxy, glass/epoxy and boron/epoxy, with different angles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Yasser et al studied with 0 0 , 30 0 , 45 0 , 60 0 and 90 0 fiber orientation of unidirectional carbon fiber -epoxy composite and found that fiber orientation influences the young's modulus (10) . Berrahou et al, studied on 8 layers of different composites with different fiber orientation and experience fiber orientation effects the ultimate strength (11) . Zhao et al, identify the direction and distributions of fibers and prepare a specimen to increase the efficiency of fiber orientation measuring operations (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Yasser et al studied with 0 0 , 30 0 , 45 0 , 60 0 and 90 0 fiber orientation of unidirectional carbon fiber -epoxy composite and found that fiber orientation influences the young's modulus (10) . Berrahou et al, studied on 8 layers of different composites with different fiber orientation and experience fiber orientation effects the ultimate strength (11) . Zhao et al, identify the direction and distributions of fibers and prepare a specimen to increase the efficiency of fiber orientation measuring operations (12) .…”
Section: Introductionmentioning
confidence: 99%